UPAYA KEPALA MADRASAH DALAM MENINGKATKAN PROFESIONALISME GURU DI RAUDHATUL ATHFAL HABIBIE SINGOSARI MALANG - Nufaisah Muniroh; Anwar Sa'dullah; Ika Anggraheni (Jurnal Dewantara, 2019)
How are teacher’s profesionalism in RA.Habibie Singosari Malang and how are the headmaster’s effort to improve teacher’s profesionalism in RA.Habinie Singosari Malang because some teachers are still not qualified. The headmaster has been, trying to make the teacher the profesional by attending workshop and training, but the profesionalism still unqualified. This research takes place in RA Habibie Singosari Malang. Also, this research used qualitative research method. In this research, the data collection is not numbers but in form of words and thought. The data collection form interview, documentation, intitution’s document and etc. The result, half of the teachers in RA Habibie Singosari Malang still unqualified as a teacher, especially in education field. So, it needs a competency test as a path to improve the quality. The headmasters also has been trying to improve its teacher profesionalismby including to participate in routine meetings, workshops, training, supervision as well as comparative studies between institutions to improve teacher profesionalism.